2022
DOI: 10.55002/mr.2.6.39
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of meat yield and physicochemical characteristics of indigenous, cockerel and sonali chicken

Abstract: The experiment was conducted to compare the meat yield and quality characteristics of indigenous, cockerel and sonali male (Backcrossed; RIR♂ × Sonali♀) chicken weighing around 750g. The birds were slaughtered and meat yield characteristics such asbreast, thigh, drumstick, wing, liver, heart, head, gizzard, neck etc. were compared against their live weight. After that the breast, thigh and drumstick of all birds were stored at 4 ̊C to evaluate different quality characteristics at 24hour postmortem. No signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…Breast meat percentage of broiler was 21.61 as reported by Thamizhannal (2022) which supports the present findings. Similarly, 13.9% and 14.05% dressing yield was recorded by Sarker et al (2022) and Jahan et al (2015) respectively which also consistence with this study. Although, Ali et al (2022b) found lower percentage of breast muscle for both broiler and deshi chickens than present findings while Islam et al (2022) reported that percentage of breast muscle were 27.76 which is much higher than the current study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Breast meat percentage of broiler was 21.61 as reported by Thamizhannal (2022) which supports the present findings. Similarly, 13.9% and 14.05% dressing yield was recorded by Sarker et al (2022) and Jahan et al (2015) respectively which also consistence with this study. Although, Ali et al (2022b) found lower percentage of breast muscle for both broiler and deshi chickens than present findings while Islam et al (2022) reported that percentage of breast muscle were 27.76 which is much higher than the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Percentage of thigh, drumstick and wing meat in the current study is more or less similar to the results of Ferdaus et al (2015). Whereas, Jahan et al (2015) and Sarker et al (2022) found slightly higher value of thigh meat than current study. However, percentage of drumstick meat in the present findings is very close to the findings of Jahan et al (2015) and Ali et al (2022b).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Northcutt et al (1994) stated that chicken meat expounded to high temperature (40 to 41°C) lost significant amounts of drip loss during the processing period. Sarker et al (2022) observed that the drip loss value of breast and thigh meat among the three types of chicken did not show significant differences (p>0.05). Greater drip loss was observed for turkey breast muscle held at 30°C, whereas 0°C and 12°C minimized water losses (Lesiak et al, 1996).…”
Section: Drip Lossmentioning
confidence: 81%
“…This is mainly because of the ease to enter into the business as fairly moderate capital outlay is required to start (Oluwanbe, 2002). However, in the world over, there is rising operational cost, which tends heavily towards feeding of birds to the toll of about 60% of the cost (Sanni et al, 2000;Sarker et al, 2022;Sultana et al, 2023). Silver Brown are the world most prolific egg layers producing over three hundred and thirty rich brown eggs within eighteen months and are adaptable to tropical environment (Parkhaurst and Mountney, 2004), but they consume more for them to produce the desired eggs in terms of number and size as well as furnish considerable dressing yield.…”
Section: Introductionmentioning
confidence: 99%